Waste collection vehicle routing problem benchmark datasets and case studies: A review - Idrus, Zanariah; Ku-Mahamud, Ku Ruhana; Benjamin, Aida Mauziah (JATIT, 2017)
Waste collection vehicle routing problem (WCVRP) is one of the most studied areas and has received high interest from the modern society today.This corresponds to the cost efficiency, population growth, and environmental concerns.The growth of the WCVRP awareness is the result of continuous supports from government and private organizations.This paper reviews severa established benchmark datasets and successful real-life case studies. Respectively billions of dollars have been saved from the operational costs.The current trend for benchmark datasets presented and case studies are accordingly grouped by countries and continents, thus revealing the need for WCVRP. Investigation on objectives, constraints and algorithms are also discussed. Results showed the increased interest of researchers in using benchmark datasets as well as the case studies and some of the constraints that should be considered in WCVRP.It also suggested that environmental or quality of service issues can be integrated into the common objectives of minimizing cost and distance travelled.Methods used in WCVRP are exact methods and approximate methods.Results showed that approximate methods have the capability in providing good results for large-scale data. Conclusively, this study analyzes the gap and provides recommendations for researches.